Diagnostic work up for language testing in patients undergoing awake craniotomy for brain lesions in language areas. (June 2014) - Bilotta, Federico; Stazi, Elisabetta; Titi, Luca; Lalli, Diana; Delfini, Roberto; Santoro, Antonio; Rosa, Giovanni
Abstract Awake craniotomy is the technique of choice in patients with brain tumours adjacent to primary and accessory language areas (Broca's and Wernicke's areas). Language testing should be aimed to detect preoperative deficits, to promptly identify the occurrence of new intraoperative impairments and to establish the course of postoperative language status. Aim of this case series is to describe our experience with a dedicated language testing work up to evaluate patients with or at risk for language disturbances undergoing awake craniotomy for brain tumour resection. Pre- and intra operative testing was accomplished with 8 tests. Intraoperative evaluation was accomplished when patients were fully cooperative (Ramsey < 3). Postoperative evaluation was scheduled at early (within 21 days) and long-term follow-up (3–6 months). Twenty consecutive patients were prospectively recruited. Preoperative language testings were normal in 9 patients (45%), showed mild to moderate language deficit in 8 (40%) and severe language deficit or aphasic disorders in 3 (15%). Broca's area was identified in 15 patients, in all cases by counting arrest during stimulation and in 12 cases by naming arrest. In this article we describe our experience using a language testing work up to evaluate – pre, intra and postoperatively – patients undergoing awake craniotomy for brain tumour resection with preoperative language disturbances or at risk for postoperative language deficits. This approach allows a systematic evaluation and recording of language function status and can be accomplished even when a neuropsychologist or speech therapist are not involved in the operation crew.